Phenol/Chloroform-Free TiO2-Based miRNA Extraction from Cell Lysate - Smělá, Denisa; Zelinková, Eliška; Řehulka, Pavel; Bílková, Zuzana; Kupčík, Rudolf (MDPI, 2022)
While microRNAs are considered as excellent biomarkers of various diseases, there are still several remaining challenges regarding their isolation. In this study, we aimed to design a novel RNA isolation method that would help to overcome those challenges. Therefore, we present a novel phenol/chloroform-free, low-cost method for miRNA extraction. Within this method, RNA is extracted from cell lysate with an isopropanol/water/NaCl system, followed by solid-phase extraction using TiO2 microspheres to effectively separate short RNAs from long RNA molecules. We also demonstrated the pH-dependent selectivity of TiO2 microspheres towards different sizes of RNA. We were able to regulate the size range of extracted RNAs with simple adjustments in binding conditions used during the solid-phase extraction.
Extrakce miRNA z buněčného lyzátu bez fenol/chloroformu s využitím nosiče na bázi TiO2
Keywords: miRNA isolation; TiO2; phenol/chloroform-free; short RNA extraction; miRNA izolace; TiO2; extrakce krátkých RNA